Kultivasi Mikroalga Menggunakan Media Af6 Berdasarkan Perbedaan Volume Solution A Media Af6 - Febrina Adelina Sigalingging; Padil Padil; Sri Rezeki Muria (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Microalgae are microscopic plant organisms that live in waters. Nutrition is one of the important factors for the growth of microalgae. Optimization of nutrition is expected to increase the growth of microalgae. In cultivating laboratory scale microalgae, AF6 media is used as a source of nutrition. One stock of AF6 media material is solution A contains lots of nitrogen. This research purpose for determining the effect of the difference in volume of AF6 media solution A on growth rate and doubling time of various microalgae cultivated in AF6 media. In this research observations of cell density microalgae Chlorella sp. (6) and Chlamydomonas sp. (4, 5, 19, chl) on the volume of solution A media AF6 2, 3 and 4 ml were carried out by UV-VIS spectrophotometer with a wavelength of 680 nm. The results showed that specific growth rate highest and shortest doubling time occurs on the addition of a volume of 4 ml of solution A AF6 media. Microalgae that have a highest specific growth rate and shortest doubling time are Chlamydomonas sp. Microalgae. (19) 0.91/day and 0.75/day, respectively. Therefore, microalgae Chlamydomonas sp. (19) can be cultivated on a commercial scale to be processed into the products we want.Keywords: lipids, microalgae, AF6 media, optical density, solution A